EMPIRICAL VALIDITY AND INTERNAL CONSISTENCY TESTING OF MODIFIED ONLINE LEARNING READINESS SCALE (OLRS) - Rohim, Agil Abdur; Purwati, Oikurema; Anam, Syafiul; Suhartono, Suhartono (TELL - US JOURNAL, 2023)
Five dimensions of Online Learning Readiness Scale (OLRS) offers convincing quantification of online students’ readiness. Its modification, the addition of two more dimension, is even claimed to be applicable for blended learning environment. Nonetheless, quality of modified OLRS is questionable. Therefore, the purpose of this study is to assure the quality of OLRS after the modification. In order to do so, empirical validity and internal consistency testing were conducted. 42 participants were included for the testing. The result showed that there are four items which needs special attention. The reliability value is also slightly decreased, from .85 to .74. The value is not ideal, but still widely acceptable for research usage. In short, the OLRS modification insignificantly reduces the quality of its psychometric properties. Further research is recommended by the author to focus on reformulating the items in order to enhance its empirical validity and reliability simultaneously, or conducting other statistical test to maintain the quality of OLRS.